Oracle essentials : Oracle database 10g - Greenwald, Rick (O'Reilly, 2004)
Distilling a vast amount of knowledge into an easy-to-read volume covering the full range of Oracle's features and technologies, this title includes an overview of Oracle 10g, along with recent releases 9i and 8i. It provides everything you should need to install and run the Oracle databases.